Extraction of lipids and eicosapentaenoic acid from Nannochloropsis oceanica biomass using ionic liquid-based microwave-assisted extraction method - Motlagh, Shiva Rezaei (2020)
The consumption of omega-3 polyunsaturated fatty acids (PUFAs), especially eicosapentaenoic acid (EPA, 20:5n-3), have some therapeutic impacts on human health. The combination of ionic liquids (ILs) with MAE revealed significant attention in comparison to conventional toxic solvents for biomass lipid extraction. Therefore, this study analyzes the suitable ILs for extracting EPA from microalgae, Nannochloropsis oceanica. The scope of the study includes screening of ILs solvents to be used using computational COSMO-RS, extracting the lipids from the microalgae, evaluating the kinetics and the thermodynamics of the extraction process as well as manipulating the extraction process for optimum EPA yield. It was found that among the investigated ILs, a combination of tetramethyl ammonium with SO4 or Cl was the best fit for EPA extraction. Three selected ILs, namely [EMIM][Cl], [TMAm][Cl], and [EMPyrro][Br], were empirically selected based on results provided by COSMO-RS software. The validation results pinpointed the good prediction capabilities of COSMO-RS. Furthermore, the study investigates the effect of different extraction parameters of MAE with ILs including solid-loading, irradiation time, irradiation power, extraction temperature, and IL amount on the total lipid extraction yield and EPA content from microalga Nannochloropsis oceanica. The results of the screening study shown that the highest amount of total lipid yield and EPA content for all examined ILs were extracted with examined ILs mediated in water-based microwave irradiation at the ILs amount of 2 g, 25 min, 90 °C and 1 g of ILs amount, 25 min, 90 °C, respectively. The optimum extraction conditions, the yield of total extracted lipids and the content of EPA were found 19.58 wt% (gr/gr of total biomass) and 37.919 mg/g of total biomass respectively, when the extraction process was accomplished in 24.69 min at 88.18 °C and with 1.65 g of [TMAm][Cl]. Furthermore, at similar condition, the total lipid and EPA were extracted in the order of: [TMAm][Cl] > [EMPyrro][Br] > [EMIM][Cl]. Under these experimental conditions, total SFAs, MUFAs and PUFAs composition after ILs based MAE were respectively 28.49 wt%, 27.99 wt% and 40.63 wt% for [TMAm][Cl], which the high percentage of PUFAs make it a potential feedstock for pharmaceutical production. Also, [TMAm][Cl] mediated in water medium based microwave irradiation had improved the total lipid yield and EPA content around 2.53 times and 7.85 times at the optimum condition in comparison to the standard extraction method of Soxhlet which was extracted total lipid around 7.75% and 4.83 mg/g of EPA. Among the mathematical models used, Second-order rate law and Patricelli model with highest R2 of 0.9823 and 0.968 were recognized as the most suitable model for explanation of extraction processes of [TMAm][Cl] based microwave irradiation of EPA extraction. The values of thermodynamic parameters such as Gibbs free energy change (ΔG), enthalpy change (ΔH) of +403.0557 (kJ/mol.K), and entropy change (ΔS) of + 0.1485 (kJ/mol.K) indicate that this process is endothermic, irreversible, and spontaneous, respectively. Overall, the IL-MAE method promises a cheaper, greener, and faster extraction process for a high-quality lipid and EPA from microalgae.